Mechanical performance of structurally optimized AlSi7 aluminum foams – an experimental study. Issue 12 (4th December 2014) - Lehmhus, D.; Busse, M.; von Hehl, Axel; Weise, Jörg
<x xml:space="preserve">Abstract</x> AlSi7 aluminum foams produced via the powder compact melting process suffer from deficiencies in the pore structure that are linked to the mismatch between the decomposition temperature range of the common blowing agent TiH2 and the solidus and liquidus temperature of the matrix alloy. To alleviate these deficiencies, two main paths have been discussed in the past: One is the adaptation of the matrix alloy towards lower melting temperatures, the other the modification by heat treatment of the foaming agent itself, which leads to higher decomposition temperatures. The present paper compares the mechanical response of foams produced according to the second approach to that of the reference material, AlSi7 foamed using untreated TiH2 as blowing agent. Mechanical performance is evaluated based on uniaxial, quasi‐static compression tests over a wide range of densities. In parallel, the pore and microstructure of the respective materials is characterized using metallographic sections and computed tomography for image acquisition, as well as image analysis to derive quantitative parameters. Foams based on thermally treated blowing agents show increased compressive strength at technically relevant density levels. The advantage is lost at very high porosities in excess of 85–90% only.